The Implementation of Android-Based Application as a Media for Teaching English in Simple Present Tense - Dewi Yana; Farahdila Fajar Darwati (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This research was conducted to figure out whether the implementation of android–based application can improve students’ understanding in simple present tense and to find out the responses of students toward the implementation of the media. This classroom action research is done at the eighth grade students of Fatmawati Learning and Education Center (FLEC) in academic year 2016/2017. It contained 15 students in the classroom. This study had two cycles done and used tests, field notes and interview as the instruments to gather the data. The finding of the research shows that there are significant improvements of students’ achievements since the implementation of the media until the last cycle of the research. It was proved by the improvement resulted in two cycles. According to the results, there are significant improvements in each cycle. The result of pre-test showed that there were only two students or 13.33% passed the exam. The mean of pre-test was 55.67. From the result of first cycle, it can be concluded that there is 28.13% improvement of the result from pre-test. It is proven by the improvement of classroom success and mean. In the first cycle, classroom success is 53.33% and the mean increased to be 71.33. The last cycle is cycle two. It was successful by the result of students. There are 13 students were successful passing the exam and only two students failed. It gave result to the classroom success about 86.67% with the score mean 84. The study also results responses from students toward the media usage in the classroom from students’ interview and field notes. From students’ interview, researcher concluded that the implementation of android-based application as media for teaching in the classroom could solve the problem and increase students’ understanding in learning simple present tense.  Based on the data of field notes, researcher found positive and desired response from the students during the observation. It was observed from verbal and non-verbal responses shown by the students.